Hyphenated Analytical Methods in Determination of Biologically Active Compounds in Hen's Eggs. (3rd May 2016) - Walczak, Justyna; Bocian, Szymon; Trziszka, Tadeusz; Buszewski, Bogusław
ABSTRACT: Hen's egg is a complete material needed for the development of the embryo; it is an important source of nutraceutical compounds, such as protein, fats, vitamins, trace metals, and minerals. Moreover, avian egg contains biologically active compounds that exhibit antibacterial and antimicrobial activities as well as antitumor, antiviral, antioxidant, immunomodulating, and therapeutic properties. Eggs are mostly very good sources of valuable, easily digestible proteins. This review focuses on the biologically active compounds from hen's egg and applications of these compounds in medicine and the pharmaceutical industry. Additionally, it gives an overview of the hyphenated separation techniques, including sample preparation, analysis, and identification, used in the proteomics and lipidomics analysis.